PENENTUAN WILAYAH SENTRA INDUSTRI KOMODITAS UNGGULAN KABUPATEN SERAM BAGIAN TIMUR - Rumata, Nini (Jurnal Karajata Engineering, 2021)
The knowledge and appreciation of the Indonesian people for the multifunctionality of fisheries, plantations and agriculture is still very low. The function of this commodity, which has been known to the public, is only to produce commodity products with low economic value. In addition, the socio-economic conditions of people who are located far from industrial centers have a habit of requiring immediate income, as well as the social structures that have been formed causing difficulties in the development of value added produced by farmers and fishermen. Determination of industrial center areas that cannot reach the entirety of East Seram Regency will have an impact on the low level of welfare and income inequality of farmers or fishermen. The purpose of this study is to determine the centers of leading commodity industry in the East Seram District. This research is a qualitative and quantitative research with descriptive and causal comparative approaches. The analysis used is Spatial Multi Criteria Analysis by combining the process hierarchy analysis and spatial analysis with the overlay method. The expected result of this research is the location of industrial centers for superior commodities in the East Seram Regency so that it can improve the welfare of the community, especially farmers and fishermen.